Mobile Number Portability: A Study of Consumer Perceptions and Factors Influencing Adoption in Pakistan - Ahmad, Yasir Zamir (2009)
The widespread diffusion and use of mobile telephony has been heralded as the dawn of a ‘personal communication society’, triggering new forms of social networking and coordination that have accelerated social change (Campbell & Park, 2008). For many, the mobile telephone number has become their identity, and the only channel of communication with the rest of the world. Mobile number portability (MNP) is a technology through which mobile subscribers can switch service providers while retaining their mobile numbers. It is recognized as a key instrument in ensuring market competitiveness of mobile operators, and allowing consumers to maximize their utility by ensuring freedom of choice in using mobile services. This paper studies MNP through a model of the user acceptance of technology. Using constructs from established models, a framework is developed to determine the factors that shape behavioral intention to use MNP. To test this framework, mobile subscribers in Pakistan are surveyed to gather data about the perceptions of MNP, satisfaction with existing cellular service provider, and intention to adopt MNP. The results of this study hold significant implications for policy implementers and mobile network operators, and will be useful for future research in this area.